Analisis Perlakuan Akuntansi atas Persediaan Barang Dagangan pada PT Traktor Nusantara - Wike Ariska; Rizqy Fadhlina Putri (Jurnal Multidisiplin Madani, 2022)
This study was to determine the accounting treatment of merchandise inventory at PT. Traktor Nusantara which includes recording, appraising, acknowledging and presenting inventories is in accordance with the Statement of Financial Accounting Standards (PSAK) No. 14 about supplies. The type of research used is descriptive qualitative. The subjects in this study were PT. Traktor Nusantara with the object of research is recording and reporting. The data collection technique used in this study was in the form of observation, namely direct observation of the situation at the research site, interviews, namely obtaining information by way of questioning and answering the staff and documentation. Based on the results of the research as a whole, it shows that there is a discrepancy in the recording of the purchase freight expense in determining the cost of goods sold